Comprehensive Health and Environmental Risk Assessment of Zanjan Lead-Zinc Hydrometallurgy Tailings - Hamed Biglari; Seyyed Mohammad Mousavi; Kamyar Yaghmaeian; Mohammad Hadi Dehghani; Ramin Nabizadeh Nodehi; Shahrokh Nazmara; Mahmood Alimohammadi (Results in Engineering)
The hydrometallurgical tailings, with their extreme geochemical characteristics, severely threaten global environmental integrity and human health. Report on their pollution levels could serve as a crucial alarm, demanding greater attention and action. This study investigated the concentrations and corresponding risk assessments of potentially toxic Metal(loid)s—arsenic (As), cadmium (Cd), mercury (Hg), manganese (Mn), chromium (Cr), lead (Pb), zinc (Zn), copper (Cu), nickel (Ni), and cobalt (Co)—in tailings from the Zanjan Zinc-Lead Hydrometallurgy Industrial Park (ZZLHIP), utilizing established indices such as the Contamination Factor (Cf), Modified Contamination Degree (mCd), Pollution Load Index (PLI), Geoaccumulation Index (Igeo), Hazard Index (HI), and Environmental Failure Mode and Effects Analysis (EFMEA) to evaluate potential risks. Results revealed severe metal(loid) contamination, with concentrations ordered as Zn > Co > Pb > Mn > As > Cu > Cd > Ni > Hg > Cr, extending up to 5 km east and southwest of ZZLHIP, indicating widespread tailings dispersion. The mCd (300.64) and PLI (70.58) values signify 'ultra to extremely pollution, with Cf and Igeo identifying Hg and As as major pollutants. Health risk assessments highlighted oral ingestion as the primary exposure pathway, posing significant non-carcinogenic risks to children and adults. Carcinogenic risks were elevated for As, moderate for Cr, Co, and Pb, and minimal for Ni and Cd. EFMEA identified wind and precipitation as key pollution dispersal drivers. These findings emphasize the urgent need for remediation to address the substantial environmental and health risks posed by ZZLHIP tailings, offering critical insights for policymakers and stakeholders.